Examining of the presence and frequency of the impulse control disorders in Wilson’s disease - Nikolić, Ana (Medicinski podmladak, 2024)
ABSTRACT Introduction: Wilson’s disease is rare, hereditary disease, which leads to the accumulation of copper, primarily in liver and brain, due to the impossibility of its excretion from the body. The disease is presented with hepatic, neurological and psychiatric symptoms. Neurological form of the disease includes the following forms: parkinson-like, dystonic, cerebellar and mixed form.Aim: To determine the presence and frequency of impulse control disorder and other psychiatric symptoms in Wilson’s disease.Material and methods: This is an opservational study in which we examined consecutive patients who were treated at the UKCS Neurology Clinic, Belgrade. Respodents were surveyed with following questionnaires and scales: Questionnaire for impulsive-compulsive disorders, Beck Depression Scale, Hamilton’s Anxiety Scale, Apathy Scale, Impulsivity Scale, Questionnaire for obsessive-compulsive symptoms. Demographic data were taken from the subjects and severity of disease was assessed using the Unified Wilson Disease Rating Scale. Results: A total of 7 out of 25 patients were classified as WB-PKI+ and 18 of them as WB-PKI-. We did not find a statistically significant difference in the scales assessing the severity of the disease and the behavioral and cognitive characteristics between the two groups. The logistic regression model for the diagnosis of impulse control disorders was significant and a higher score on apathy scale emerged as a significant predictor. Statistical analysis showed that there is a higher apathy scale score and a lower MMSE score in patients with dystonic form of disease. Results show that patients with mixed form of disease have higher score on impulsivity scale. Sperman's test shows that there is a statistically significant correlation between length and severity of the illness and apathy scale.Conclusion:Patients with Wilson's disease are affected by various impulse control disorders in 28% of patients, with those who have more severe symptoms of apathy being at increased risk.Key words:Wilson’s disease; impulse control disorder; impulsiveness; apathy